Fault Stability Across the Seismogenic Zone. Issue 8 (3rd August 2020) - Aubry, J.; Passelègue, F. X.; Escartín, J.; Gasc, J.; Deldicque, D.; Schubnel, A.
Abstract: Across the seismogenic zone, the transition from brittle to plastic deformation corresponds to a semibrittle regime where brittle fracturing and plastic flow coexist at high strength conditions. Thorough experimental investigations on brittle‐plastic transition are crucial to understand why natural faults behave in stable or unstable ways at varying crustal depths and why large earthquakes generally nucleate at the base of the seismogenic zone. To investigate semibrittle deformation in carbonates and the conditions promoting it, we reported here the results of experiments performed on Carrara marble saw cut faults in triaxial conditions. We studied the influence of the confining pressure (ranging between 45 and 180 MPa), axial loading rates (0.01 and 1 μm s −1 ) and initial fault roughness (smooth and rough) on fault (in‐)stability across the brittle‐plastic transition. We conclude that laboratory earthquakes may nucleate on inherited fault interfaces at brittle‐plastic transition conditions. The occurrence of laboratory earthquakes associated with increasing plastic deformation is promoted at high confining pressure, on smooth fault interfaces, or when the loading rate is slow. In a rather counterintuitive manner, increasing initial roughness promotes stable sliding and a larger amount of plastic deformation. Furthermore, we show that stable sliding tends to produce mirror‐like surfaces, while stick‐slips are associated with matte surfaces, on which the size of the asperities grows with increasing confining pressure. Finally, our results seem to reveal the influence of asperity hardness and melt viscosity on fault weakening. Plain Language Summary: The regime where both brittle and plastic deformation processes are active is known as the semibrittle regime. Understanding fault stability within this regime is crucial because large earthquakes nucleate at the base of this intermediate regime. To look at the slip behavior of fault surfaces within the semibrittle regime, we performed experiments on simulated faults made of Carrara marble, a rock standard prone to be deformed in the semibrittle field at room temperature and pressure conditions of the Earth's upper crust in the laboratory. Through distinctive seismic cycle experiments on artificial laboratory faults, we investigated slip behavior (stable slip, slow slip, or stick‐slip) as a function of pressure, background loading rates, and initial roughness. We conclude that (i) fault slip behavior is controlled by fault roughness, (ii) plastic deformation can coexist with the occurrence of laboratory earthquakes (i.e., unstable faults) within the semibrittle regime, and (iii) asperity hardness and melt viscosity influence slip weakening. Key Points: Fault slip behavior is mainly controlled by roughness and asperity nucleation size Plastic deformation can coexist with the occurrence of laboratory earthquakes Fault weakening initiation depends on asperity hardness while weakening efficiency depends on melt viscosity